Posttraumatic Stress Disorder Symptoms and Suicide Risk in Male Firefighters: The Mediating Role of Anxiety Sensitivity. Issue 3 (March 2018) - Boffa, Joseph W.; Stanley, Ian H.; Smith, Lia J.; Mathes, Brittany M.; Tran, Jana K.; Buser, Sam J.; Schmidt, Norman B.; Vujanovic, Anka A.
Abstract : Abstract: Posttraumatic stress disorder (PTSD) symptoms are positively related to suicide risk among firefighters. One mechanism that may account for this relationship is anxiety sensitivity (AS) cognitive concerns—the fear that cognitive symptoms of anxiety will have catastrophic consequences. We sought to replicate the mediating effect of AS cognitive concerns on the relationship between PTSD symptoms and suicide risk among 214 trauma-exposed male firefighters with non-zero suicide risk. Bootstrap mediation analyses tested AS cognitive concerns as a statistical mediator of PTSD symptoms (total and symptoms clusters scores) and suicide risk, controlling for depression symptoms and relevant demographic variables. AS cognitive concerns statistically mediated the relationship between PTSD symptoms (total score, as well as intrusion, avoidance, and arousal-reactivity symptoms clusters) and suicide risk; however, the reverse was also true. AS cognitive concerns may confer risk for suicide among trauma-exposed firefighters. Firefighters may benefit from AS-specific interventions, which are shown to reduce PTSD symptoms and suicidality.